The Quality of Arabica Coffee Beans Evaluation at Various Processing in Luwu Regency South Sulawesi, Indonesia. Issue 1 (1st June 2022) - Wibowo, Nendyo Adhi; Djufry, Fadjry; Syafaruddin,; Iflah, Tajul; Dani,
Abstract: Arabica coffee plantations in Luwu Regency are planted at elevations above 1, 000 mdpl, so that the Arabica coffee clones planted can produce high-quality coffee flavors. The aims of this study were to determine the physical, chemical, and taste profile of Arabica coffee Luwu in order to increase the added value and competitiveness of the product. The research was conducted using a survey method on Arabica coffee plantations in Latimojong District, Luwu Regency, South Sulawesi Province. Sampling using purposive random sampling method and analyzed in duplicate. Samples of coffee variants were obtained from several farmers and from several levels of the coffee trade system around Luwu Regency. Analysis of physical quality characters includes levels of live insects, foul-smelling seeds/mold, moisture content, dirt content, and special quality requirements on seed size, number of seed chips, and defect values. The chemical analysis includes water, ash, caffeine, protein, and fat. The taste of brewed coffee in an organoleptic manner refers to the Specialty Coffee Association of America/SCA standard covering aroma/fragrance, flavor, body, acidity, aftertaste, sweetness, balance, clean cup, uniformity, and overall. Based on the results of the study, the coffee beans met the general quality requirements, there were no live insects, no foul-smelling and/or moldy beans, moisture content of 12.5%, and a maximum dirt content of 0.5%. The value of ash content is 4.344%-5.514%, fat content is 11.194%-14.067%, the highest protein content is 11.687%-13.719%, the highest caffeine content is 0.041%-0.064%. The results of the taste test showed that ten samples had the potential for specialty coffee with a score above 8 and two samples below a score of 8.